Giving comfort, dispelling fear: social welfare at the shrine of Data Ganj Bukhsh in Lahore, Pakistan - Strothmann, Linus (ERDKUNDE, 2013)
Based on the case study of Pakistan’s largest Sufi Shrine, Data Darbar, situated in Lahore, this paper explores ways in which sacred places can be used by diverse actors for social welfare. As blessings (barraka) from the saint/shrine are connected to much of the social welfare, services are not exclusively used by the poor, taking away any stigmatisation of those relying on these services. Although Data Darbar is one of the most important centres of social welfare in Pakistan, Western development agencies have so far overlooked the groups involved especially the Faith Based Organisations (FBOs). The reason for this lies in the general neglect of Islamic institutions as part of civil society due to their negative image as the example of the Pakistani madrasas shows. Apart from being a centre of social welfare, the shrine has also become a place of risk due to suicide attacks in 2010. However, the shrine continues to be a place of comfort rather than a place of fear, because the belief in the saint gives visitors and those providing social welfare a strong psychological resilience. The paper therefore suggests that sacred places and FBOs be included more often in the debate on security, resilience and development in South Asia.